A Qualitative Assessment of the Determinants of Faculty Engagement in Internationalization: A Chinese Perspective. (September 2021) - Li, Hui; Khattak, Shoukat Iqbal; Jiang, Qingquan
Faculty is the key agent for internationalization. This interview-based study explored faculty views about the internationalization understanding, rationales, roles, engagement, and motivation in a research-centric, double-first class university in China. Faculty motivation was analyzed using the lens of the motivation systems theory (MST). The main findings concerning the five main themes emerging from the analysis of documents and interviews of twenty-eight faculty members are as follows. First, Chinese faculty's understanding, rationales, roles, engagement, and motivation were significantly influenced by the national and university policies. Second, they mainly understood internationalization as activities, openness, and cross-cultural exchange. Third, unlike other countries, Chinese faculty espoused a broader scope of internationalization in their rationales, spanning from personal to university, higher education, China, and world development. Fourth, faculty perceived roles in internationalization included main drivers, role models, liaisons, and coordinators. Fifth, faculty motivation comprised goals, beliefs, and emotions. Faculty, among other goals, aspired to improve teaching content and expand students and self-abilities, yet they had mixed context and capacity beliefs. For example, they appreciated the university and national support for international travel, funding, and research but criticized complex travel procedures and teaching evaluation methods. They also felt concerned about their teaching, research, and communicating in a foreign language with students and international peers, except those with foreign backgrounds and experience. Faculty experienced different emotions when undertaking international activities, for example, joy, interest, and excitement to explore and learn. Finally, there was a high-medium level of faculty engagement in teaching and research than service internationalization (low or no engagement).